Urgensi implementasi three line of defense dalam industri perbankan syariah di Indonesia - Khatimah, Khusnul (Maliki Interdisciplinary Journal, 2024)
The Islamic banking industry in Indonesia has experienced significant growth in recent years. This growth brings positive impacts as well as new challenges, especially related to risk management. To address these challenges, the Three Lines of Defense approach has been recognized as an effective framework in banking risk management. This article aims to illustrate the urgency of implementing the Three Lines of Defense in the context of the Islamic banking industry in Indonesia